Global burden of lower respiratory infections attributable to cytomegalovirus, 1990–2021: a systematic analysis from the MICROBE database - Zhang, Wanwan; Liu, Min; Ji, Haoyu; Mensah, Emmanuel; Li, Shirong; Wang, Hanli; Lu, Zhiwei; Wei, Shuoshuo; Cheng, Yusheng; Zha, Lei (Frontiers in Microbiology, 2025)
ObjectivesThis study aimed to investigate the global epidemiological characteristics and disease burden of lower respiratory infections (LRIs) attributable to cytomegalovirus (CMV) from 1990 to 2021.MethodsWe systematically assessed the global burden and temporal trends of CMV-associated LRIs across different ages, sexes, geographic regions, and socioeconomic statuses using data from the MICROBE database spanning 1990–2021. Key metrics included mortality, disability-adjusted life years (DALYs), and their corresponding age-standardized rates (ASRs)ResultsGlobally, the number of DALYs due to CMV-attributed LRI decreased from an estimated 734,208 (95% UI: 612,175–856,241) in 1990 to 530,465 (95% UI: 469,046–591,884) in 2021, while the number of deaths increased from 16,141 (95% UI: 14,247–18,034) to 19,235 (95% UI: 17,204–21,266) over the same period. The age-standardized DALY rate (ASDR) declined from 13.89 (95% UI: 11.86–15.93) in 1990 to 6.95 (95% UI: 6.08–7.83) in 2021. Similarly, the age-standardized mortality rate (ASMR) dropped from 0.40 (95% UI: 0.35–0.44) to 0.24 (95% UI: 0.21–0.27). In 2021, the disease burden was highest in regions with low Socio-demographic Index (SDI). From 1990 to 2021, both ASMR and ASDR for CMV-attributable LRI decreased as SDI increased, and projections indicate a continued decline over the next 30 years.ConclusionsThe global burden of CMV-attributable LRI has declined significantly from 1990 to 2021. However, targeted and cost-effective interventions are urgently needed to prevent and reduce the burden of CMV-associated LRI, particularly in low-SDI regions, children, and the elderly.